PEMAKNAAN KHALAYAK TERHADAP PERFORMATIVITAS GENDER DALAM FILM KUCUMBU TUBUH INDAHKU - Erica Pinasthika, Emilia; Hasfi, Nurul; Manalu, Rouli (Interaksi Online, 2024)
This study was conducted to understand the interpretation of millennial parents in Semarang City regarding gender performativity in the film "Kucumbu Tubuh Indahku." Gender performativity based on Judith Butler's perspective views gender as non-binary, where individuals may enact their gender differently over time based on their experiences and contexts. This qualitative descriptive research used Stuart Hall's reception analysis method to discover the audience's reception towards gender performativity in “Kucumbu Tubuh Indahku” and John Fiske's semiotic analysis to identify the preferred readings offered by "Kucumbu Tubuh Indahku”. The result revealed that (1) Tolerance towards gender diversity can be accepted by the public to achieve gender inclusivity. (2) Audiences encountered certain limitations in accepting gender performativity due to conflict with their cultural and religious beliefs (3) There is a correlation between the individuals’ background and their acceptance towards gender performativity. The research findings indicate that the audiences' backgrounds shape their receptions towards media (film).